Kisah Rama dan Sinta, Makna Filosofis, Pengorbanan, dan Kesetiaan dari Perspektif Teologi Kristen - Manalu, Hery Buha (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes the story of Rama and Sinta from the Hindu tradition with a Christian theological approach, focusing on philosophical meaning, sacrifice, and loyalty as universal values. Using the critical hermeneutic method, this study reveals that Rama's sacrifice reflects selfless love that is in line with the teachings of Jesus Christ, while Sinta's loyalty reflects the commitment of Christians to God. This discussion shows the cross-cultural relevance of Hindu narratives and Christian faith, as well as the importance of interfaith dialogue in enriching cultural theology. The results of the study indicate that the values in this story not only contribute to theological appreciation, but are also relevant in the development of value education in a multicultural society. This study confirms that the story of Rama and Sinta can be a source of inspiration for Christians to apply universal virtues such as sacrifice and loyalty in everyday life.